PPA1 Promotes Breast Cancer Proliferation and Metastasis Through PI3K/AKT/GSK3β Signaling Pathway - Guo, Chunlei; Li, Shuang; Liang, Ang; Cui, Mengchao; Lou, Yunwei; Wang, Hui (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer is the most common malignancy among women. Inorganic pyrophosphatase 1 (PPA1) is a multifunctional protein involved in the development of several tumors. However, the role of PPA1 in breast cancer progression remains unclear. In this study, we found that PPA1 was highly expressed in breast cancer compared to its levels in normal breast tissue and that it was correlated with breast cancer clinicopathological characteristics, as well as poor survival in breast cancer patients. Silencing PPA1 restrained breast cancer proliferation and metastasis by regulating Slug-mediated epithelial-mesenchymal transition (EMT) in vitro and in vivo. Opposite results were observed following PPA1 overexpression. In addition, investigation of the underlying mechanism demonstrated that PPA1 ablation led to decrease phosphatidylinositol 3 kinase (PI3K) phosphorylation levels and attenuate phosphorylated AKT and glycogen synthase kinase-3 β (GSK3β), while ectopic PPA1 expression had the opposite effects. Moreover, PI3K inhibitors suppress the signaling pathways mediating the effects of PPA1 on breast cancer, resulting in tumor growth and metastasis suppression in vitro and in vivo. In summary, our results verify that PPA1 can act as an activator of PI3K/AKT/GSK3β/Slug-mediated breast cancer progression and that it is a potential therapeutic target for the inhibition of tumor progression.